2021
DOI: 10.2106/jbjs.20.02141
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Surgical Site Infection on Patient Outcomes After Open Posterior Instrumented Thoracolumbar Surgery for Degenerative Disorders

Abstract: Background:Few reports in the literature have described the long-term outcome of postoperative infection from the patient perspective. The aim of the present study was to determine if complicated surgical site infection (SSI) affects functional recovery and surgical outcomes up to 2 years after posterior instrumented thoracolumbar surgery for the treatment of degenerative disorders.Methods:This retrospective cohort study involved patients who had been enrolled in a previous randomized controlled trial that exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…The authors found that the development of SSI did not lead to a difference in outcome scores at 1-year follow-up from spinal fusion. These findings mirror those recently published by Urquhart et al , 3 who report the negative impact of SSI after surgery resolves at 1-year follow-up using the same outcome measures.…”
supporting
confidence: 91%
“…The authors found that the development of SSI did not lead to a difference in outcome scores at 1-year follow-up from spinal fusion. These findings mirror those recently published by Urquhart et al , 3 who report the negative impact of SSI after surgery resolves at 1-year follow-up using the same outcome measures.…”
supporting
confidence: 91%
“…There have been many articles on the topical of local vancomycin to reduce the risk of infection after orthopaedic surgery [3,38,39]. Moreover, vancomycin impregnated bone graft has been also widely used in spinal surgery [40][41][42]. Therefore, a prospective randomized study with an adequate patient number is needed to clarify the benefits of vancomycin impregnated autogenous bone graft and bone substitute on preventing DSSI following degenerative lumbar spine fusion surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Our re-revision risks tended to be lower (22% versus 56%) in favor of the occult infection group, even though the difference was not statistically significant. In general, surgical site infections not only require enduring long-term antibiotic treatment, but are also associated with poorer clinical outcome scores and higher risk for revision surgery [ 35 , 36 ]. Therefore, we expected that the occultly infected patients would have lower PROMs together with higher re-revision risk when compared to their noninfected study group.…”
Section: Discussionmentioning
confidence: 99%